A Numerical and Experimental Investigation of the Effects of Cutting Fluid on Machining Performance - Chowdhury, Sayem Ahmed (Curtin University, 2016)
Cutting fluids play an important role in improving machining performance. However, cutting fluids have adverse effects on health and environment. A new methodology has been proposed for the prediction of tool temperature and the experimentally validated methodology revealed that turning operations can be performed with reduced amount of cutting fluid. Followed by, experiments were conducted and the results demonstrated that the reduce amount of cutting fluid is sufficient to obtain acceptable machining performance.